The relationship between race pattern and performance in the men's 400 m sprint - Yamamoto, K.; Miyashiro, K.; Naito, H.; Kigoshi, K.; Tanigawa, S.; Ohyama Byun, K.; Miyashita, K.; Ogata, M. (Japan Journal of Physical Education, Health and Sport Sciences, 2014)
This study was conducted to clarify the relationship between race pattern and performance in the men's 400-m race. Using several video cameras, 154 male 400-m sprinters (45-46 s: 26, 47 s: 35, 48 s: 58, 49 s: 35) in official competitions were videotaped at a sampling rate of 59.94 Hz from the start to the finish. The split time at every 50 m from the start was calculated using the Overlay method, which analyzes the split time by superimposing an image of the 400-m race onto an image of the hurdles in a 400-m hurdle race. Each segment was defined as follows: First segment, from the start to the 100-m mark; 2nd segment, from the 100-m mark to the 200-m mark; 3rd segment, from the 200-m mark to the 300-m mark; 4th segment, from the 300-m mark to the finish. The results of regression analysis revealed significant correlations between the 400-m race time and the all of the segment times (r=0.589-0.887, p<0.001), the ratio of the time for the 3rd segment (r=0.290, p<0.001) to that of the 4th segment (r=0.218, p<0.01), the rate of change in running speed from the 1st to the 2nd segments (r=-0.317, p<0.001), and that from the 2nd to the 3rd segments (r=-0.271, p<0.01). However, the relationship between the 400-m race time and the deceleration index (the slope of the linear relationship between running speed and the number of segments from the peak running speed to the finish) was not significant (r=0.154, p=0.056). These results suggest that it is important to maintain running speed in the 2nd and 3rd 100-m segments to achieve high performance in the 400-m sprint